Remote ischemic conditioning to protect against ischemia-reperfusion injury: a systematic review and meta-analysis. - Daniel Brevoord; Peter Kranke; Marijn Kuijpers; Nina Weber; Markus Hollmann; Benedikt Preckel (PLoS ONE)
Background Remote ischemic conditioning is gaining interest as potential method to induce resistance against ischemia reperfusion injury in a variety of clinical settings. We performed a systematic review and meta-analysis to investigate whether remote ischemic conditioning reduces mortality, major adverse cardiovascular events, length of stay in hospital and in the intensive care unit and biomarker release in patients who suffer from or are at risk for ischemia reperfusion injury. Methods and results Medline, EMBASE and Cochrane databases were searched for randomized clinical trials comparing remote ischemic conditioning, regardless of timing, with no conditioning. Two investigators independently selected suitable trials, assessed trial quality and extracted data. 23 studies in patients undergoing cardiac surgery (15 studies), percutaneous coronary intervention (four studies) and vascular surgery (four studies), comprising in total 1878 patients, were included in this review. Compared to no conditioning, remote ischemic conditioning did not reduce mortality (odds ratio 1.22 [95% confidence interval 0.48, 3.07]) or major adverse cardiovascular events (0.65 [0.38, 1.14]). However, the incidence of myocardial infarction was reduced with remote ischemic conditioning (0.50 [0.31, 0.82]), as was peak troponin release (standardized mean difference -0.28 [-0.47, -0.09]). Conclusion There is no evidence that remote ischemic conditioning reduces mortality associated with ischemic events; nor does it reduce major adverse cardiovascular events. However, remote ischemic conditioning did reduce the incidence of peri-procedural myocardial infarctions, as well as the release of troponin.